Education Supervision at Madrasah - Bahrudin, Muhammad; Yasminar, Fegy Diah (International Journal on Advanced Science, Education, and Religion, 2025)
This study discusses madrasa educational supervision as a developmental process aimed at improving the quality of learning and teacher professionalism through constructive, democratic, and continuous supervisory practices. The article comprehensively examines the concept of supervision, the factors influencing its implementation, the objectives and functions of supervision in madrasas, the various types of supervision, the processes involved, as well as the techniques, approaches, and methods applied. The findings indicate that madrasa educational supervision functions not only as a mechanism of control, but also as a strategic effort to integrate religious and general curricula, enhance teachers’ competencies, foster a collaborative working environment, and strengthen institutional governance. Effective supervision requires the active involvement of madrasa principals, teachers, and supervisors in carrying out their respective roles based on the principles of cooperation and continuous professional guidance. Therefore, madrasa educational supervision can serve as an essential means of achieving educational quality that is aligned with Islamic values while also addressing the challenges of modern education.